P2Y12 Receptor Inhibitors in the Treatment of Patients with Acute Coronary Syndrome and Percutaneous Coronary Intervention: Possibilities of Prasugrel - N. M. Vorobyeva (Рациональная фармакотерапия в кардиологии)
The possibilities of P2Y12 receptor inhibitors application in the treatment of patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) are discussed in the article. The results of 4 registries in which a comparative analysis of the efficacy and safety of prasugrel with clopidogrel or ticagrelor was performed, as well as of all 3 P2Y12-receptor inhibitors among themselves, are considered in detail. The feasibility of replacing clopidogrel to prasugrel during the inpatient treatment of patients with ACS and PCI was evaluated additionally in the MULTIPRAC registry. The results of the registries demonstrate that the use of prasugrel in patients with ACS and PCI is associated with a significant reduction in the risk of ischemic complications and mortality with an acceptable risk of bleeding. At the same time, prasugrel was more effective and safer than clopidogrel and at least was non-inferior to ticagrelor, and according to some registries, even surpasses it in a number of indicators.